A kind of high purity quartz sand and preparation method thereof
By performing supercritical CO2 ball milling and segmented hot press leaching treatment of NH4Cl-H2SO4 system on quartz sand, the problem of improving purity of quartz sand in the prior art is solved, especially the removal effect of elements such as Na, B, and Zr, so as to achieve the realization of The high purity preparation of quartz sand has reached 99.999%.
Patent Information
- Application Number
- CN202411411780.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-11
AI Technical Summary
It is difficult to obtain higher purity quartz sand in the prior art, especially the removal effect of elements such as Na, B, Zr is poor, and it is difficult to further improve the purity of quartz sand.
The segmented hot press leaching method using supercritical CO2 ball milling and NH4Cl-H2SO4 system includes roasting and water quenching treatment, ball milling is carried out under supercritical conditions using CO2 gas, and hot press leaching is carried out through NH4Cl-H2SO4 system. Adjust the NH4Cl concentration and leaching time to improve the purity of the quartz sand.
The removal effect of Mg, Ti, Ca, P, B, and Zr elements was significantly improved, and the removal effect of Al and Fe elements was further improved, so that the purity of quartz sand reached 99.999%.
Smart Images

Figure CN118908230B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of quartz sand purification and relates to high-purity quartz sand and a preparation method thereof. Background Art
[0002] High-purity quartz sand is quartz sand with SiO2 content higher than 99.9%. It is white powder, no different color, and has very low impurity content. It has high temperature resistance, excellent chemical properties, excellent electrical insulation and light transmittance, etc. It is an irreplaceable mineral raw material for high-tech industries. The purification of quartz sand mainly removes a small amount or trace impurities to obtain high-purity quartz sand. Iron oxide and aluminum oxide are the main harmful substances in quartz sand. Therefore, the effective removal of iron and aluminum can significantly reflect the technological progress of quartz sand purification and process. Commonly used processes include scrubbing, gravity separation, magnetic separation, flotation, acid leaching, etc. Quartz is insoluble in acid (except hydrofluoric acid). Through the dissolution of iron and other harmful elements by acid, impurities are separated to obtain high-purity quartz sand. Compared with the HCl-HF system or the NH4Cl-HF system, the NH4Cl-H2SO4 system avoids the addition of fluorine, a dangerous element, and can also purify quartz sand better. For example, CN111874915A discloses a method for preparing high-purity quartz sand using vein quartz as raw material, comprising the following steps: (1) subjecting the vein quartz ore to magnetic separation and impurity removal to obtain a non-magnetic product; (2) washing the non-magnetic product with a dilute hydrochloric acid solution to obtain a vein quartz concentrate; (3) preparing the vein quartz concentrate into a slurry, adjusting the pH of the slurry to 2-4, and then adding dodecylamine to the slurry for flotation treatment; (4) roasting the vein quartz concentrate after flotation at 700-1100°C for 5-11 hours, and after roasting, quenching the vein quartz concentrate with water; (5) mixing the roasted and water-quenched vein quartz concentrate with a leaching solution and performing a hot-pressing leaching treatment, wherein the hot-pressing leaching temperature is 220-280°C and the hot-pressing leaching time is 4-8 hours, and the leaching solution is a mixture of a sulfuric acid solution and an ammonium chloride solution. However, the NH4Cl-H2SO4 system has a good removal effect on elements such as Al, K, Fe, S in quartz sand, and has a certain removal effect on elements such as Mg, Ti, Ca, P, but has a poor removal effect on elements such as Na, B, Zr, and it is difficult to obtain quartz sand with higher purity. Summary of the invention
[0003] The purpose of the present invention is to obtain quartz sand with higher purity. To this end, the present invention provides a high-purity quartz sand and a preparation method thereof to solve this need in the art.
[0004] On the one hand, the present invention relates to a method for preparing high-purity quartz sand, comprising: hot-pressing and leaching quartz sand after roasting and water quenching, wherein the hot-pressing and leaching adopts an NH4Cl-H2SO4 system;
[0005] Before the calcination, the quartz sand is placed in CO2 gas, ball-milled and dried under supercritical conditions.
[0006] Furthermore, in the preparation method of high-purity quartz sand involved in the present invention, the supercritical condition is the condition that CO2 is in a supercritical CO2 fluid state, the gas pressure is not less than 7.5MPa, and the temperature of the ball mill is 35~40℃.
[0007] Furthermore, in the method for preparing high-purity quartz sand of the present invention, the rotation speed of the ball mill is 300-600 rpm, and the time is 6-10 hours.
[0008] Furthermore, in the method for preparing high-purity quartz sand of the present invention, the pulverizing medium used in the ball mill is zirconia balls, and the wet grinding agent is deionized water.
[0009] Furthermore, in the method for preparing high-purity quartz sand of the present invention, the ball-to-material ratio during ball milling is 50-100:1.
[0010] Furthermore, in the method for preparing high-purity quartz sand of the present invention, the hot-pressing leaching comprises performing a first hot-pressing leaching, washing with deionized water and then drying, and then performing a second hot-pressing leaching, washing with deionized water and then drying;
[0011] The NH4Cl concentration of the first hot-press leaching is 1.0-1.5 mol / L, and the leaching time is 1-2 h;
[0012] The NH4Cl concentration of the second hot-pressing leaching is 0.3-0.5 mol / L, and the leaching time is 5-6 h.
[0013] Furthermore, in the preparation method of high-purity quartz sand involved in the present invention, the parameters of the first hot pressing leaching or the second hot pressing leaching are independently selected from: leaching temperature of 250~300℃, H2SO4 concentration of 0.2~0.6mol / L, and liquid-to-solid ratio of 4~7mL / g.
[0014] Furthermore, in the method for preparing high-purity quartz sand of the present invention, the calcination temperature is 900-1000° C. and the calcination time is 5-6 hours;
[0015] The water quenching is to use deionized water to quickly cool and dry immediately after the roasting is completed.
[0016] Furthermore, in the method for preparing high-purity quartz sand of the present invention, any of the drying steps is independently vacuum drying at 100-120°C.
[0017] On the other hand, the present invention relates to high-purity quartz sand, which is prepared by any of the methods for preparing high-purity quartz sand, and the purity of the high-purity quartz sand is not less than 99.99%.
[0018] Compared with the prior art, the technical solution provided by the present invention has at least the following beneficial effects or advantages:
[0019] The present invention has been verified through experiments that the quartz sand is treated with supercritical CO2 and then roasted and water quenched, and finally the NH4Cl-H2SO4 system is used for hot pressure leaching to improve the purity of the quartz sand. This can synergistically improve the removal effect of the NH4Cl-H2SO4 system on Mg, Ti, Ca, P, B, and Zr elements, and further improve the removal effect of Al and Fe elements.
[0020] Ammonium salts, especially ammonium chloride, are more stable than many organic complex catalysts under high temperature and high pressure conditions, and will not introduce metallic impurity elements. Nitrogen-containing impurities can also be removed by simple later processes. When the NH4Cl-H2SO4 system is hot-pressed and leached to improve the purity of quartz sand, the relationship between the removal effect of Al and Fe elements and the NH4Cl concentration presents a V-shaped curve. The present invention is based on the relationship between different NH4Cl concentrations and the element removal effect when the NH4Cl-H2SO4 system is hot-pressed and leached to improve the purity of quartz sand, and adopts a segmented hot-pressed leaching method, so that the NH4Cl-H2SO4 system is further improved in removing the Al and Fe elements. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 This is the relationship between NH4Cl concentration and total element impurity removal rate.
[0023] Figure 2 This is a graph showing the relationship between reaction time and total element impurity removal rate. DETAILED DESCRIPTION
[0024] The technical scheme of the present invention is described below in conjunction with the embodiments, but the present invention is not limited to the following embodiments. The experimental methods and detection methods described in each embodiment are conventional methods unless otherwise specified; the reagents and materials can be purchased on the market unless otherwise specified. The % in the following embodiments, unless otherwise specified, are all mass percentages. The ratios in the following embodiments, unless otherwise specified, are all mass ratios.
[0025] Example 1
[0026] This embodiment provides a method for improving the purity of quartz sand by hot pressure leaching using a conventional NH4Cl-H2SO4 system.
[0027] The quartz sand samples (particle size of 100-200 μm) were taken for chemical composition analysis using inductively coupled plasma spectrometry and mass spectrometry. The analysis results of the impurity element content in the quartz sand samples are shown in Table 1.
[0028] Table 1: Impurity element content in quartz sand samples (μg / g)
[0029]
[0030] As shown in Table 1, the total content of impurity elements in the quartz sand sample is 622.10μg / g, and the purity of SiO2 is 99.9378%. Among them, the Al element content is 372.10μg / g, the K element content is 105.09μg / g, and the Fe element content is 63.49μg / g, accounting for 86.91% of the total impurity content, which are the main impurity metal elements in the quartz sand sample.
[0031] Calcination and quenching: Place the quartz sand sample in a quartz boat and calcine it at 900°C for 6 hours. After taking it out, quickly cool it with deionized water and vacuum dry it in a vacuum drying oven at 100°C for later use.
[0032] The optimal parameters for hot-pressure leaching of the NH4Cl-H2SO4 system are as follows: 10.000 g of quartz sand sample is placed in the high-pressure leaching reaction device, the NH4Cl concentration is controlled to be 0.4 mol / L, the H2SO4 concentration is controlled to be 0.4 mol / L, the leaching temperature is 280 °C, the liquid-solid ratio is 5 mL / g, and the reaction time is 7 h.
[0033] Table 2: Removal rate of impurity elements in quartz sand samples (%)
[0034]
[0035] As shown in Table 2, the NH4Cl-H2SO4 system has a good removal effect on elements such as Al, K, Fe, and S in quartz sand, a certain removal effect on elements such as Mg, Ti, Ca, and P, and a poor removal effect on elements such as Na, B, and Zr. Under the optimal parameter conditions, quartz sand with a SiO2 purity of 99.99% can be obtained, but it is difficult to obtain quartz sand with higher purity.
[0036] With the total element impurity removal rate (%) as the ordinate and the NH4Cl concentration as the abscissa, and other conditions fixed, the relationship between the NH4Cl concentration and the total element impurity removal rate is obtained as shown in the figure below: Figure 1shown.
[0037] Depend on Figure 1 It can be seen that with the increase of NH4Cl concentration, the removal rate of total element impurities shows a trend of first increasing, then decreasing, and then increasing again. When the NH4Cl concentration is 0.4mol / L, the removal rate reaches a relatively high level, but when the NH4Cl concentration continues to increase to 0.7mol / L, the removal rate decreases instead, and when the NH4Cl concentration continues to increase to 1.0mol / L, the removal rate continues to rise. This may be because the NH4Cl-H2SO4 system exerts different removal mechanisms when the NH4Cl concentration ranges are different.
[0038] With the total element impurity removal rate (%) as the ordinate and the reaction time as the abscissa, and other conditions fixed (NH4Cl concentration fixed at 0.4 mol / L), the relationship between reaction time and total element impurity removal rate is obtained as shown in the figure below: Figure 2 As shown. Figure 2 It can be seen that with the increase of reaction time, the removal rate of total elemental impurities gradually increases, but when the reaction time increases to 8h, the removal rate of total elemental impurities decreases again.
[0039] Example 2
[0040] This embodiment provides a method for improving the purity of quartz sand by hot-pressing leaching of the NH4Cl-H2SO4 system provided by the present invention.
[0041] Supercritical CO2 treatment: The quartz sand sample is placed in CO2 gas, ball-milled and dried under supercritical conditions; the gas pressure is 7.5 MPa, the temperature of the ball mill is 35°C; the speed of the ball mill is 450 rpm, and the time is 8 hours; the crushing medium is zirconia balls, and the wet grinding agent is deionized water.
[0042] After the supercritical CO2 treatment, the sample was placed in a vacuum drying oven and dried at 100°C before being taken out.
[0043] The quartz sand sample after removal was roasted, quenched and hot-pressed by NH4Cl-H2SO4 system with optimal parameters according to Example 1.
[0044] Example 3
[0045] This embodiment provides a method for improving the purity of quartz sand by hot-pressing leaching of the NH4Cl-H2SO4 system provided by the present invention.
[0046] The quartz sand sample was calcined, quenched and hot-pressed with the NH4Cl-H2SO4 system with the optimal parameters according to Example 1; the difference was that the hot-pressing leaching was adjusted to the first hot-pressing leaching, followed by washing with deionized water and drying in a vacuum drying oven at 100°C, and then the second hot-pressing leaching was performed, followed by washing with deionized water and drying in a vacuum drying oven at 100°C; the NH4Cl concentration of the first hot-pressing leaching was 1.2 mol / L, and the leaching time was 1.5 h; the NH4Cl concentration of the second hot-pressing leaching was 0.4 mol / L, and the leaching time was 5.5 h.
[0047] Example 4
[0048] This embodiment provides a method for improving the purity of quartz sand by hot-pressing leaching of the NH4Cl-H2SO4 system provided by the present invention.
[0049] Supercritical CO2 treatment: The quartz sand sample is placed in CO2 gas, ball-milled and dried under supercritical conditions; the gas pressure is 7.5 MPa, the temperature of the ball mill is 35°C; the speed of the ball mill is 450 rpm, and the time is 8 hours; the crushing medium is zirconia balls, and the wet grinding agent is deionized water.
[0050] After the supercritical CO2 treatment, the sample was placed in a vacuum drying oven and dried at 100°C before being taken out.
[0051] The quartz sand sample after removal was roasted, quenched and hot-pressed by NH4Cl-H2SO4 system with optimal parameters according to Example 1.
[0052] The hot pressing leaching was adjusted to perform the first hot pressing leaching, followed by washing with deionized water and drying in a vacuum drying oven at 100°C, and then perform the second hot pressing leaching, followed by washing with deionized water and drying in a vacuum drying oven at 100°C; the NH4Cl concentration of the first hot pressing leaching was 1.2 mol / L, and the leaching time was 1.5 h; the NH4Cl concentration of the second hot pressing leaching was 0.4 mol / L, and the leaching time was 5.5 h.
[0053] Example 5
[0054] This embodiment provides a method for improving the purity of quartz sand by hot-pressing leaching of the NH4Cl-H2SO4 system provided by the present invention.
[0055] Supercritical CO2 treatment: The quartz sand sample is placed in CO2 gas, ball-milled and dried under supercritical conditions; the gas pressure is 8.0 MPa, the temperature of the ball mill is 40°C; the speed of the ball mill is 300 rpm, and the time is 6 hours; the crushing medium is zirconia balls, and the wet grinding agent is deionized water.
[0056] After the supercritical CO2 treatment, the sample was placed in a vacuum drying oven and dried at 100°C before being taken out.
[0057] The quartz sand sample after removal was roasted, quenched and hot-pressed by NH4Cl-H2SO4 system with optimal parameters according to Example 1.
[0058] The hot pressing leaching was adjusted to perform the first hot pressing leaching, followed by washing with deionized water and drying in a vacuum drying oven at 100°C, and then perform the second hot pressing leaching, followed by washing with deionized water and drying in a vacuum drying oven at 100°C; the NH4Cl concentration of the first hot pressing leaching was 1.0 mol / L, and the leaching time was 1 h; the NH4Cl concentration of the second hot pressing leaching was 0.3 mol / L, and the leaching time was 5 h.
[0059] Example 6
[0060] This embodiment provides a method for improving the purity of quartz sand by hot-pressing leaching of the NH4Cl-H2SO4 system provided by the present invention.
[0061] Supercritical CO2 treatment: The quartz sand sample is placed in CO2 gas, ball-milled and dried under supercritical conditions; the gas pressure is 8.0 MPa, the temperature of the ball mill is 40°C; the speed of the ball mill is 600 rpm, and the time is 10 hours; the crushing medium is zirconia balls, and the wet grinding agent is deionized water.
[0062] After the supercritical CO2 treatment, the sample was placed in a vacuum drying oven and dried at 100°C before being taken out.
[0063] The quartz sand sample after removal was roasted, quenched and hot-pressed by NH4Cl-H2SO4 system with optimal parameters according to Example 1.
[0064] The hot pressing leaching was adjusted to perform the first hot pressing leaching, followed by washing with deionized water and drying in a vacuum drying oven at 100°C, and then perform the second hot pressing leaching, followed by washing with deionized water and drying in a vacuum drying oven at 100°C; the NH4Cl concentration of the first hot pressing leaching was 1.5 mol / L, and the leaching time was 2 h; the NH4Cl concentration of the second hot pressing leaching was 0.5 mol / L, and the leaching time was 6 h.
[0065] After testing, the removal rate of impurity elements in the purified quartz sand was calculated in Examples 2 to 6, and the test results are shown in Table 3.
[0066] Table 3: Removal rate of impurity elements in quartz sand samples (%)
[0067]
[0068] It can be seen from Table 3 that supercritical CO2 treatment can effectively improve the removal effect of NH4Cl-H2SO4 system on Mg, Ti, Ca, P, B, and Zr elements, while segmented hot-pressing leaching can further improve the removal effect of Al and Fe elements. Supercritical CO2 treatment and NH4Cl-H2SO4 system hot-pressing leaching can synergistically improve the removal of impurities in quartz sand and produce quartz sand with SiO2 purity of 99.999%.
[0069] As described above, the basic principle, main features and advantages of the present invention are well described. The above embodiments and descriptions are only descriptions of the preferred implementation modes of the present invention, and the present invention is not limited by the above embodiments. Without departing from the spirit and scope of the present invention, various changes and improvements made by ordinary technicians in this field to the technical solution of the present invention should fall within the protection scope determined by the present invention.
Claims
1. A method for preparing high-purity quartz sand, comprising: The quartz sand after roasting and water quenching is subjected to hot-pressing leaching, wherein the hot-pressing leaching adopts an NH4Cl-H2SO4 system, characterized in that before the roasting, the quartz sand is placed in CO2 gas, ball-milled and dried under supercritical conditions; The supercritical condition is a condition where CO2 is in a supercritical CO2 fluid state, the gas pressure is not less than 7.5MPa, and the temperature of the ball mill is 35-40°C; The hot pressing leaching comprises performing a first hot pressing leaching followed by washing with deionized water and then drying, and then performing a second hot pressing leaching followed by washing with deionized water and then drying; The NH4Cl concentration of the first hot-press leaching is 1.0-1.5 mol / L, and the leaching time is 1-2 h; The NH4Cl concentration of the second hot-press leaching is 0.3-0.5 mol / L, and the leaching time is 5-6 h.
2. The method for preparing high-purity quartz sand according to claim 1, characterized in that: The ball mill has a rotation speed of 300-600 rpm and a milling time of 6-10 hours.
3. The method for preparing high-purity quartz sand according to claim 1, characterized in that: The grinding medium used in the ball mill is zirconium oxide balls, and the wet grinding agent is deionized water.
4. The method for preparing high-purity quartz sand according to claim 3, characterized in that: The ball-to-material ratio during ball milling is 50-100:
1.
5. The method for preparing high-purity quartz sand according to claim 1, characterized in that: The parameters of the first hot-pressing leaching or the second hot-pressing leaching are independently selected from: leaching temperature of 250-300° C., H 2 SO 4 concentration of 0.2-0.6 mol / L, and liquid-to-solid ratio of 4-7 mL / g.
6. The method for preparing high-purity quartz sand according to claim 1, characterized in that: The calcination temperature is 900-1000°C and the calcination time is 5-6 hours; The water quenching is to use deionized water to quickly cool and dry immediately after the roasting is completed.
7. The method for preparing high-purity quartz sand according to any one of claims 1 to 6, characterized in that: Any of the drying steps is independently vacuum drying at 100-120°C.
8. A high-purity quartz sand, characterized in that: The high-purity quartz sand is prepared by the preparation method of high-purity quartz sand according to any one of claims 1 to 7, wherein the purity of the high-purity quartz sand is not less than 99.99%.
Citation Information
Patent Citations
Method for preparing high-purity quartz sand with vein quartz as raw material
CN111874915A